Pemanfaatan Limbah Kulit Buah Pinang (Areca chatecu L.) Sebagai Biosorben untuk Mengolah Logam Berat Pb (II) - Lisa Utami; Lazulva Lazulva (Al-Kimia, 2017)
This research aims to investigate the utilization of the waste of Pinang Fruit peel as a biosorbent which function to process Pb (II) from contaminated water. The result showed that the absorbtion ability of Pb (II) was strongly influenced by the acidity of solution, contact duration and the initial concentration of the Pb (II) solution. The maximum absorbtion was 92,50% at pH 6, initial concentration of 50 ppm in 75 minutes contact time. FTIR spectral data indicated the presence of  amina, alcohol and carbonil groups. Isotherm Langmuir was at the maximum absorbtion of 0,877 mg/g.